Valuing Language and Culture: An Example From Sasak - Mahyuni, Mahyuni (UI Scholars Hub, 2007)
No one disputes that possession of language is one of the most distinctive of all human cultural attributes. The most fundamental argument has to do with the nature of language as social practice. An attempt to divorce language from its cultural context is to ignore the social circumstances which give it resonance and meaning. In the case of Sasak, language use reinforces the existing status differential and social value of language associated with the group. This perspective is employed, in this paper, to tackle the issue of Sasak language and culture.